The dark art of syphilis serology - an analysis of testing algorithms at a UK reference laboratory. Issue 4 (22nd April 2022) - Scobie, Antonia; Brown, Colin S.; French, Patrick; Donati, Matthew; Muir, Peter; Templeton, Kate; Higgins, Stephen P.; Patel, Hemanti; Alexander, Sarah; Fifer, Helen
Abstract : Introduction. Due to the complex nature of treponemal serology interpretation, testing algorithms vary across the UK. Gap statement. There is currently no gold standard method for interpretation of discordant serology results. Aim. To analyse serological response in early infection and to determine the best approach for discordant total antibody EIA and TPPA samples. Methodology. National reference laboratory serology and PCR (genital ulcer swabs) results from 2010 to 2017 were extracted from an electronic laboratory database. Results. A total of 24149 sera underwent analysis. Of syphilis PCR positive cases with contemporaneous sera, 33% (17/52) were IgM positive/equivocal, whilst all were EIA and TPPA positive. No sera with isolated IgM positivity (0/90) demonstrated seroconversion consistent with early treponemal infection, in contrast to 17% (2/12) of sera with isolated TPPA positivity. Isolated EIA positivity was observed in 6.2% (1499/24149) samples with the same result on repeat testing in 73% (154/211). In 100 samples with discordant EIA/TPPA results, IgG Immunoblot was more commonly positive (12/41, 29%) or equivocal (24/41, 59%), in those with a higher EIA antibody index, compared to those with a low antibody index, of which none tested positive and 2/3 (67 %) were equivocal. Conclusion. Isolated IgM positivity was not helpful in identifying early infection; isolated total antibody EIA positivity is unlikely to be a significant finding. IgG immunoblot testing was unable to determine clear treponemal antibody status in nearly half of all EIA/TPPA discordant samples.